THE REFLECTION OF SOCIETY REFLECTED IN FOLK MUSIC: लोक संगीत में झलकता समाज का प्रतिबिम्ब - Srivastava, Kinshuk; Dyondi, Rashmi p (International Journal of Research -GRANTHAALAYAH, 2015)
Culture is found in human society. This culture is transferred from one generation to another. That is why the culture of every society survives. The culture of each society is rooted in language, custom, knowledge, traditions, religion, law, music, folk art, folk music, folk tales, literature etc. Human interactions in society affect each other and it is on the basis of these actions that a cultural society is formed. Therefore, the mirror of the society lies in the folk culture itself. "Music is the most popular in the tradition of culture." Folk music is a huge variety of culture. The language of folk music is simple, tunes easy and heart-rending for the entertainment of the general public of the society. Daily activities of human society, plowing, cattle grazing, grinding mill, cowling. Fishing water from wells, wedding marriages, christenings, festivals, festivals, natural places, sweltering fields, the sound of river flowing water, waterfalls, waterfalls, waterfalls, rain, spring season, blooming colorful flowers, etc. Natural events origin of folk songs Places are "" For folk songs, Shriram Tripathi has adopted the word ’Gramgeet’. The experience behind calling folk songs as village songs is that only rural people have preserved the tradition of folk songs. The place of various rites and festivals associated with Indian life is relatively low in urban life, so the songs sung on various occasions are getting destroyed without the opportunity to sing while the countryside still has enthusiasm for festivals and festivals. Therefore, at the time of sowing, harvesting, nairai, marriage and marriage of fields, these songs are spontaneously released from their hearts. These melodious waves of folk music do not cease to be heard only at these festivals and fairs and festivals, but these enchanting taunts constantly resonate in the lives of the people who live here. Folk music holds an integral place even on occasions ranging from human birth to death. Folk songs are automatically created from the heart of the common people at various times, filled with different emotions according to different circumstances. Hence, folk music is a simple mood expression of an ordinary person living in society with tone, rhythm and rhythm. मानव समाज में संस्कृति पायी जाती है। यह संस्कृति एक पीढ़ी से दूसरी पीढ़ी को हस्तान्तरित होती रहती है। इसी कारण प्रत्येक समाज की संस्कृति जीवित रहती है। प्रत्येक समाज की संस्कृति भाषा, प्रथा, ज्ञान, परम्पराएँ, धर्म, कानून, संगीत, लोक कला, लोक-संगीत, लोक-कथाएँ, साहित्य आदि में निहित होती हैं। समाज में मनुष्य की पारस्परिक अन्तः क्रियाएँ एक-दूसरे को प्रभावित करती है तथा इन्हीं क्रियाओं के आधार पर ही सांस्कृतिक समाज बनता है। अतः समाज का दर्पण लोक संस्कृति में ही निहित है। ‘‘संस्कृति की परम्परा में संगीत सबसे अधिक लोकप्रिय है। लोक संगीत संस्कृति की विशाल विभूति है। समाज के जनसाधारण के मनोरंजनार्थ लोक संगीत की भाषा सरल, धुनें सहज एवं हृदय ग्राहय होती है। मानव समाज की दैनिक क्रिया, हल चलाना, पशु चराना, चक्की पीसना, गोड़ना। खेते नियरानों कुओं से पानी भरना, शादी ब्याह, नामकरण, उत्सव, त्यौहार, प्राकृतिक स्थल लहलहाते खेत, नदी के बहते जल की ध्वनि, झर-झर झरते झरने, वर्षा, बसंत ऋतु ,खिलते रंग बिरंगे फूल आदि प्राकृतिक घटनाएँ लोक गीतों के उद्गम स्थल हैं ‘‘लोक गीतों के लिये श्रीराम त्रिपाठी जी ने ‘ग्रामगीत’ शब्द को अपनाया है। लोक गीतों को ग्रामगीत कहने के पीछे यह अनुभव है कि ग्रामीण लोगों ने ही लोकगीतों की परम्परा को सुरक्षित रखा है। भारतीय जीवन से संबद्ध विभिन्न संस्कार व उत्सवों का स्थान शहरी जीवन में अपेक्षाकृत कम है, अतः नाना अवसरों पर गाए जाने वाले गीत गाने के अवसर पाए बिना नष्ट हो रहे हैं जबकि देहातियों के लिए अभी भी उत्सवों ,त्यौहारों के किए उत्साह है। अतः खेतों की बुआई, कटाई, नियराई, शादी ब्याह के समय, अनायास ही उनके हृदय से ये गीत निःसृत हो जाते हैं। लोक संगीत की ये स्वर लहरियाँ इन्हीं त्यौहारों तथा मेले व पर्वाें पर ही सुनाई देकर समाप्त नहीं होती बल्कि ये मनमोहक ताने यहाँ के बसने वाले जनसाधारण के जीवन में निरन्तर गूँजती है। मानव जन्म से लेकर मृत्यु तक के अवसर पर भी लोक संगीत अभिन्न स्थान रखता है। लोक गीत विभिन्न परिस्थिति अनुसार अलग-अलग भावनाओं से भरपूर अनेक समय पर जन साधारण के हृदय से स्वतः ही निर्मित होते चले जाते हैं। अतः लोक संगीत समाज में रहने वाले साधारण व्यक्ति की स्वर, लय व ताल युक्त साधारण मनोभावाभिव्यक्ति है।